Design of Metals Sulfides with Carbon Materials for Supercapacitor Applications: A Review. Issue 4 (4th March 2021) - Iqbal, Muhammad Faisal; Ashiq, Muhammad Naeem; Zhang, Meng
Abstract : Supercapacitors are very exclusive among energy‐storage devices for the wearable and portable industry. Due to simplicity, abundance occurrence, good electrical conductivity, and rich redox states, metal sulfides have a significant impact in supercapacitor applications in the present decade. Sulfur is the anion, associated with metal cations, and provides substantial tunable electrochemical, electrical, physical, and chemical properties in metal sulfides. In addition, carbonaceous materials enhance the electrochemical characteristics of metal sulfides synergistically for supercapacitors. Fast and scalable synthesis and fabrication of the supercapacitor cell with low‐cost metal sulfides and heterostructures should be developed to achieve the potential applications of these hybrid glorious materials. Herein, the significant and critical discussion of metal sulfides synthesis and their hybrid with carbon electrode structures for supercapacitor applications is disclosed. The realistic synthesis of metal sulfides, basic charge storage phenomena to elaborate the electrode nature, electrochemical properties including a single electrode, and asymmetric and symmetric cells are demonstrated for comparative purposes. The market values and application of supercapacitors are also elaborated. Herein, a better understanding to fresh readers about metal sulfide hybrid electrode structures for supercapacitors is provided. Abstract : Due to their simple synthesis, good electrical conductivity, and multiredox states, metal sulfide electrode structures have a great impact in supercapacitor applications. Herein, a good chance to the fresh reader to understand supercapacitors as well as good ideas for experts to elucidate metal sulfide‐secured carbon materials for supercapacitors is provided.